Real time strategy : when strategic foresight meets artificial intelligence - Schühly, Andreas; Becker, Frank; Klein, Florian (Emerald Publishing Limited, 2020)
In today's world, decision makers struggle to make good long-term decisions. There is simply too much volatility, too much complexity, too much fake news, and too little time to make sense of all the information that is at our fingertips. We are drowning in data, surrounded by uncertainty and thus live in a world that lacks clarity. Moving away from the static thinking of many strategists, this book updates and upholds the importance of scenario design and thinking in the face of uncertainty. The authors investigate the journey of the art and science of scenario thinking, from its beginnings in the military to becoming a part of the mainstream strategy toolkit in the business world. Delving into the new frontiers of scenario thinking and planning, the book explores topics such as: Human intuition The analysis and reflection process Hybrid decision platforms Social media sensing Artificial Intelligence. Combining classical scenario thinking (the gentle art of perception) with the analytical power of big data and artificial intelligence, Real Time Strategy presents the decision making of the future which enables decision makers to develop dynamic strategies, monitor their validity, and react faster.
Includes index.
Keywords: Strategic planning.; Artificial intelligence.; Business & Economics -- Strategic Planning.; Business strategy.; elektronické knihy; electronic books